Evaluating the Educational Video Materials for Radiation Education on Nursing Students and Nurses: A Quasi-Experimental Research - Minoru Osanai; Yoshiko Nishizawa; Yuka Noto; Ryoko Tsuchiya (Nursing Reports)
Background/Objectives: Although medical radiation practice is essential for current medical care, many nursing students and nurses lack sufficient basic knowledge about radiation, and they are unfamiliar with learning about it. This study aimed to evaluate the usefulness of self-made video teaching materials for radiation education for nursing students and nurses after clarifying their basic knowledge of radiation. Methods: Educational video materials were developed to provide basic radiation knowledge. The video materials included scenes of radiation measurement, such as the attenuation of scattered X-rays with distance, and illustrations drawn by nursing students to make them familiar to nursing staff. This study included 29 nursing students and 16 nurses. The participants were instructed to answer 20 questions regarding the characteristics of radiation and its influence and protection measures. The same questions were asked again after watching the video materials. Results: Nursing students and nurses correctly recognized the classification of medical or occupational exposure and the three principles for reducing external exposure; however, it became clear that dose limits do not apply to medical exposure and that radiation units and their effects on the human body were not correctly recognized. Furthermore, the educational materials were effective because the scores and the percentage of correct answers increased after viewing the video materials. Furthermore, positive comments were expressed regarding the scenes of the experiments and the illustrations drawn by the students about the teaching materials. Conclusions: The contents that should be addressed more intensively were clarified, and the effectiveness of using video teaching materials in radiation nursing education was demonstrated.